Over-the-Counter Drug Causing Acute Pancreatitis. (May 2020) - Parvataneni, Swetha; Essrani, Rajesh; Mehershahi, Shehriyar; Essrani, Rajesh; Lohana, Ajeet Kumar; Mehmood, Asif
Acute pancreatitis is caused by alcohol, gall stone disease, drugs, trauma, infections, and metabolic causes such as hypercalcemia and hyperlipidemia. Hypercalcemia-induced acute pancreatitis has been well documented but only rarely occurs due to over-the-counter calcium carbonate. In this article, we present a case of over-the-counter calcium carbonate–induced acute pancreatitis.